Pemberkasan Pemagangan Bagian Kelola Pegawai Nontetap dalam Pengelolaan Sumber Daya Manusia pada PDAM Surya Sembada Kota Surabaya - Dayyan Ramadhan Santoso; Dyah Widowati (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The development of the world of work now requires a lot of Human Resources to be able to master various skills or abilities in order to have a good impact on an organization or company. An organization is a group of individuals who work interdependently towards a goal. Individuals will be able to work interdependently only through communication. Effective communication is very important for an organization. In connection with filing in an organization, of course there is archiving. Archives are recorded information created or received in any activity or function of an organization. The purpose of writing this article is to explain the apprenticeship application process at PDAM Surya Sembada, Surabaya City. The type of research in this article is descriptive with a qualitative approach using field studies. Field studies are direct review activities aimed at obtaining the data needed as material in preparing the final report. This research includes observation and interview methods.